UO2 fuel pin bowing effects on isotopic concentrations. (July 2017) - Li, J.; Rochman, D.; Herrero, J.; Vasiliev, A.; Ferroukhi, H.; Pautz, A.; Seidl, M.; Janin, D.
Highlights: 3D advanced simulations of pin bowing by SERPENT-2 Monte Carlo Code. Investigation of radially averaged bowing effects evolving with burn-up. Quantification of isotope variation on azimuthal and axial pin profiles. Moderation modification and axial power variation account for burn-up difference. Abstract: The effects of the fuel pin bowing are simulated in a 3 × 3 pin-cells lattice to assess the possible modeling biases on isotopic concentrations during depletion calculations. The central pin in the lattice is modeled with a deformation and as a function of burn-up, characterized by a displacement in the two-dimensional (2D) lattice and a C-shape bowing in the three-dimensional (3D) lattice. The relative deviations of isotopic concentrations induced by the bowing effect are quantitatively investigated for four specific isotopes: 235 U, 239 Pu, 244 Cm and 148 Nd with the SERPENT-2 Monte Carlo code. For qualitative estimations, azimuthal and longitudinal distributions are also illustrated in the 2D and 3D models.